Pengaruh Interaktivitas Live Streaming E-Commerce dan Flash-Sale Terhadap Impulse Buying Produk Skincare : Studi Kasus pada Konsumen Shopee di Kota Malang - Mouldi Dwi Ariani; Yekie Senja Oktora; Achmad Zaini (INDO PUBLISHING, 2026)
The rapid growth of digital transactions and high internet penetration in Malang City have driven the rapid development of the Shopee Live feature as an interactive promotional tool, particularly for skincare products, one of the best-selling categories in e-commerce, so that Live Streaming interactivity and Flash-sale have the potential to trigger unplanned purchases. This study aims to examine the effect of Live Streaming E-commerce interactivity and Flash-sale, both partially and simultaneously, on Impulse Buying of skincare products among consumers in Malang City. This study used a quantitative approach with a causal research design. A sample of 100 respondents was determined through purposive sampling, with data collected using an online Likert-scale questionnaire and analyzed using multiple linear regression through SPSS. The results show that Live Streaming E-commerce interactivity and Flash-sale have a positive and significant effect on impulse buying, both partially and simultaneously. Hypothesis testing confirmed that the effect was significant at the 5% level, with both variables jointly explaining 33.5% of the variance in impulse buying. These findings indicate that the financial benefits perceived during Live broadcasts and time-limited price discounts are the main drivers of impulsive purchasing of skincare products. Therefore, Live Streaming interactivity and Flash-sale are effective marketing strategies for encouraging impulse buying, and business owners are advised to optimize Live-broadcast interactions and design more attractive Flash-sale programs.